Bleeding Time in Different Blood Groups of the ABO System- A Descriptive Cross-Sectional Study - Bam, Sanjog; Shrestha, Merina; Jyoti, Sabita; Upreti, Arish; Chaudhary, Sailesh; Joshi, Abhishek Raj (Journal of Nepalgunj Medical College, 2025)
Introduction: ABO blood grouping depends on the presence of specific antigens on red blood cell membranes: Type A, B, AB, and O have antigens a, b, both a and b, and neither a nor b, respectively. Bleeding time is the time between the puncture of vessels and to stoppage of bleeding. Certain disease seems more prevalent in specific ABO blood groups. Likewise, many studies found that blood group O and females exhibit a higher bleeding tendency.Aims: To study the bleeding time in different ABO blood groups and genders.Methods: A descriptive cross-sectional study was conducted among 139 medical students of first and second year after Ethical approval from the Institutional Review Committee of Nepalgunj Medical College Teaching Hospital, during practical hours from June to October 2025.Results: Blood group O was the most common (n=63), followed by A and B (n=28 each), and AB (n=20). Among the ABO and Rhesus factors, O-positive was most prevalent (41%), followed by A-positive and B-positive (18% each), AB-positive (12.2%), O-negative (4.3%), and the least was A-negative, B-negative, and AB-negative (2.2%). We found more Rh-positive students (90.6%) than Rh-negative (9.4%). The mean bleeding time was 2.698 minutes, with a range of 1.5 to 6.5 minutes. Non-O blood group students (n=76) consisting of Type A, B, and AB, had a shorter bleeding time compared to the O blood group, which was statistically significant. Males (n=70, mean: 2.771±.8710) had a longer bleeding time than females (n=69, mean: 2.623±.8762).Conclusion: Blood group O was predominant among the ABO group, and with the Rhesus factor, O positive was predominant. Bleeding time was prolonged in the O blood group than in any other group. Bleeding time was prolonged among males than among females.